GURU SEBAGAI PROFESI PADA PENDIDIKAN DASAR - Lis Yulianti Syafrida Siregar (DIRASATUL IBTIDAIYAH, 2021)
AbstractBase of education is one of effort for develop potential from human with professional. Substantially, reformation of education in now days is for making education back to education’s character. Teacher is an actor in education. Up till now, teacher have been made as profession but treatment to teacher not reflect that job as a teacher is profession Keywords: education, profession, teacher.